Characterisation of a customised 4-chip Timepix3 module for charged-particle tracking - Kelleter, Laurent; Schmidt, Stefan; Subramanian, M.; Marek, L.; Granja, C.; Jakubek, J.; Jäkel, Oliver; Debus, Jürgen; Martišíková, Mária (Radiation measurements, 2024)
Ion-beam radiotherapy is a growing cancer treatment modality because it offers a superior dose distribution in the patient compared with conventional radiotherapy using X-rays. Thanks to their versatility, application-specific integrated circuits (ASIC) increasingly gain interest for research into ion imaging and ion-beam characterisation. Timepix3 is a hybrid semiconductor pixel detector, which offers nanosecond time binning as well as dead-time-free and noise-free data-driven readout at a pixel pitch of 55µm × 55µm. In this work, a novel 4-chip Timepix3 mini-tracker (quad module) was characterised in a therapeutic proton beam. The quad module has two detection layers equipped with two Timepix3 chips each, which are stacked like a particle telescope at a distance of 20.3mm. In a detection layer, two Timepix3 chips share the same sensitive silicon sensor. The surface area of the silicon sensor is approximately 28mm × 14mm. Apart from the pixels at the chip edges and the masked pixels, the quad module showed a uniform counting response to the mono-energetic proton irradiation without noticeable defects. The measurement accuracy of the energy deposition was found to be better than 1% at 340keV. The synchronisation between the four chips of the quad module showed systematic delays of up to 25ns. When these delays are corrected, the time resolution of the quad module is (1.17 ± 0.03)ns. The time resolution could be further improved with the implementation of a time-walk correction. It is concluded that the quad module fulfils the requirements to be used as a charged-particle tracker in ion-beam radiotherapy. Future testing will focus on the radiation hardness, dose-rate dependence and response to high-LET radiation.